Upaya Meningkatkan Keaktifan Dan Hasil Belajar Materi Jenis-Jenis Tanggung Jawab Sebagai Warga Masyarakat Melalui Model Pembelajaran Contextual Teaching And Learning: Dengan Media Voice Note Whatsapp Pada Siswa Kelas V SDN Bonang Semester 2 Tahun Pelajaran 2020/2021 - Zaenudin, Agus (Universitas Cokroaminoto Yogyakarta, 2022)
The type of research is Classroom Action Research (CAR) which includes four components, namely planning, implementation, observation, and reflection. The research subjects were 17 students. Data collection techniques using observation techniques, tests and documentation. Validation of data using triangulation technique. The data analysis method used qualitative data analysis. The results showed an increase in student activity from 6 students or 35.29% in the initial condition, in the first cycle there were 11 students or 64.71%, and in the second cycle there were 17 students or 100%, and student learning completeness from the condition only 4 students or 23.53%, in the first cycle there were 10 students or 58.82%, and in the second cycle there were 15 students or 88.24%. The average learning outcomes increased from 58.82 to 67.06 and 77.06 in the second cycle. Based on the explanation above, it can be concluded that the CTL method with the Media Voice Note WhatsApp can increase the activity and learning outcomes of class V students at SDN Bonang Semester 2 for the 2020/2021 academic year.